Sometimes functions are defined parametrically, meaning that both y and x are given in terms of some parameter, say, t. While it may be possible to re-express a given function in terms of y and x only, you can use the chain rule to find the gradient of the function without doing this.
Using the chain rule
If your function is given parametrically, where the parameter is t, you will have two functions x(t) and y(t). To find the gradient of this function, you seek dxdy. Currently, you can find dtdx and dtdy by differentiating the parametric equations with respect to t. Using the chain rule, you have
dxdy=dtdxdtdy
You can justify this to yourself by considering the following:
dxdy×dtdx=dtdy
This rearranges to the formula above.
Example 1
Find the gradient of the curve given by the parametric equations
xy=2t+1=4t2+10t+4
Start by differentiating each of these functions with respect to t:
dtdxdtdy=2=8t+10
Thus, by the chain rule:
dxdy=28t+10=4t+5
Finally, you express this in terms of x using the original parametric equation x=2t+1. This implies that t=2x−1 and hence:
dxdy=4(2x−1)+5=2x+3
Note:It is possible to express this function non-parametrically: y=x2+3x. See that differentiating this gives the same as concluded above.
Example 2
Find the gradient at the point where x=2 of the curve given by the parametric equations
xy=3cos(θ)=sin(θ)
Differentiate each of these with respect to θ:
dθdxdθdy=−3sin(θ)=cos(θ)
Therefore, the chain rule says:
dxdy=−3sin(θ)cos(θ)
Now use the parametric equations to express this in terms of x.
You already have that cos(θ)=3x. But you can also use this to find an expression for sin(θ):